« Une fois j’ai presque rencontré un esprit » - Maddyson Borka (Ateliers d'Anthropologie)
Based on a linguistic analysis of a collection of Inuktitut stories of fortuitous meetings with spirits, the notion of meeting will be examined, and its content detailed. By taking into account the narrative structure of the stories, as well as the morphosyntactic division of certain utterances, it will be possible to highlight what it means phenomenologically to “meet” a spirit. If the stories in the collection show that a meeting with a spirit is always characterised by a paradoxical perception, their Inuktitut versions place even more emphasis on the processual and incomplete dimension of the interaction. The morphological study of utterances extracted from these stories will make it possible to explore the idea that what characterises the stories is precisely that they recount experiences that almost took place, in the sense that, although the encounter with the spirit did not fail, there might not be any witness left to talk about it.